A process for producing bacteriocin from lactobacillus plantarum. - Foo, Hooi Ling; Loh, Teck Chwen; Lim, Yin Sze; Mohd. Saleh, Norihan; Abdul Rahim, Raha; Rahmat Ali, Gulam Rusul (2004)

(untitled)
The present invention related to a process for production bacteriocin from Lactobacillus plantarum. Further, it is also relates to a method for inhibiting bacteria using bacteriocin derived from Lb. plantarum according to the present invention. The bacteriocin according to the present invention can tolerate a wide range of pH from pH 2-5 and pH 7-8. Besides, bacteriocin according to the present invention is highly antagonise against Pediococcus acidilactici, Enterococcus faecalis, Enterococcus faecium, Listeria monocytogenes ect.